2010
DOI: 10.1097/nna.0b013e3181f88fbd
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Fall-Risk Tools in Hospitalized Adults

Abstract: Meta-analysis is a useful methodology for evaluating current evidence when variation exists in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 20 publications
0
27
1
4
Order By: Relevance
“…20 Since the initial evaluation of the STRATIFY risk tool (Figure 1) in 1997, multiple studies have examined the validity of the tool. 7,[22][23][24] A meta-analysis of 12 articles on STRA-TIFY completed by Harrington et al revealed that STRATIFY may be clinically useful in the specific settings where studied, but may not have accurate clinical use outside these areas. 22 When compared to other fall risk stratification tools, the STRATIFY had lower sensitivity and higher specificity.…”
Section: Risk Stratificationmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Since the initial evaluation of the STRATIFY risk tool (Figure 1) in 1997, multiple studies have examined the validity of the tool. 7,[22][23][24] A meta-analysis of 12 articles on STRA-TIFY completed by Harrington et al revealed that STRATIFY may be clinically useful in the specific settings where studied, but may not have accurate clinical use outside these areas. 22 When compared to other fall risk stratification tools, the STRATIFY had lower sensitivity and higher specificity.…”
Section: Risk Stratificationmentioning
confidence: 99%
“…The meta-analysis by Harrington et al stated that the MFS had significantly higher sensitivity, but lower specificity than that of STRATIFY. 22 The HFRM ( Figure 3) divides patients into normal/low risk (0-2), high risk (3-6), and extremely high risk (>6) for inpatient falls. 13 The original scale had a sensitivity of 77% and specificity of 72%.…”
Section: Risk Stratificationmentioning
confidence: 99%
“…kao najpouzdanija i najpreciznija za upotrebu u akutno bolesnih hospitaliziranih odraslih pacijenata pokazuje se skala STRATIFY. Druga američ-ka studija 30 koja je uspoređivala Morseovu skalu i skalu STRATIFY osjetljivijom je procijenila Morseovu skalu, a slične rezultate dobili su i istraživači iz Južne Koreje, 28 koji su najveću prediktivnu vrijednost za identificiranje pacijenata u kojih postoji visoki rizik od pada dobili upotrebom Morseove ljestvice.…”
Section: Zaključakunclassified
“…The scales that were found to have good predictive validity for identifying potential falls are the Morse, Stratify and Schmid tools, and these are recommended for use by most health organizations. 21,23,24 All scales have one risk category in common: a history of falls. In addition, each scale includes other categories that are related to different risk factors contributing to falls.…”
Section: Factors Related To the Environmentmentioning
confidence: 99%
“…These factors include presence/absence of bed side rails, height and stability of any type of seats (including toilet seats) or obstacles such as furniture, power cables, slippery shoes, and an over-equipped patient's environment. 21,22 To assess the patient's fall risk in acute hospital settings, different fall risk assessment scales have been developed for prevention purposes. These scales are based on some of the factors related to the patient's medical condition.…”
Section: Factors Related To the Environmentmentioning
confidence: 99%